Integration of Religious and Character Education in the Independent Curriculum: Efforts to Support the SDGs in Ogan Ilir Regency - Endang Switri; M. Sirozi; Annisa Astrid; Muhammad Ndow (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to explore how the integration of religious values and character education in Islamic Religious Education (PAI) in the Independent Curriculum supports the achievement of the Sustainable Development Goals (SDGs), especially in supporting quality education (SDG 4). Theoretical framework: This study uses the theory of integration of scientific patterns, such as interdisciplinary, multidisciplinary, transdisciplinary, and value integration, to understand how religious values and character are integrated in PAI. Literature review: Character education and religious values have an important role in shaping students' morals and intellect. This study examines the integration of the two in the Islamic education curriculum, which aims not only to teach religious knowledge but also to shape the character of students. Methods: This study used a qualitative design with case studies using the analysis of PAI textbook documents and interviews with PAI teachers in high school and vocational schools. The data was analyzed using thematic analysis techniques. Results: The findings of the study show that the integration of religious values and character education in PAI has been carried out systematically in the curriculum. Values such as honesty, responsibility, empathy, and critical thinking are included in learning objectives, materials, methods, media, and evaluation. The Merdeka Curriculum emphasizes a holistic education that promotes students' academic development and character. Implications: This study shows the importance of integrating religious values and character in PAI to support the achievement of SDG 4. Teachers have an important role in instilling these values in students. Novelty: This research provides new insights into the integration of religious values and character in the Independent Curriculum, as well as its contribution to achieving sustainable development goals.